Homicide, Bereavement, and the Criminal Justice System in Texas, 2000 - Goodrum, Sarah Dugan ([Verlag nicht ermittelbar], 2001)
This study assessed the influence of the criminal justice system on the bereavement process of individuals who have lost loved ones to homicide. The primary question motivating this research was: Can the criminal justice system help to heal the harm of the bereaved's loss? The three main goals of this study were to examine: (1) bereaveds' perceptions of and experiences with the criminal justice system and its professionals, (2) the ways criminal justice professionals perceive and manage the bereaved, and (3) the nature of the association between the criminal justice system and bereaveds' psychological well-being. Data were obtained from in-depth interviews conducted in June through December 2000 with two different groups of people. The first group represented individuals who had lost loved ones to murder between 1994 and 1998 in one county in Texas (Parts 1-33). The second group (Parts 34-55) was comprised county criminal justice professionals (murder detectives, prosecutors, criminal court judges, victim's service counselors, and victim's rights advocates). For Parts 1-33, interviewees were asked a series of open-ended questions about the criminal justice system, including how they learned about the death and the current disposition of the murder case. They also were asked what they would change about the criminal justice system's treatment of them. The bereaved were further asked about their sex, age, race, education, marital status, employment status, income, and number of children. Additional questions were asked regarding the deceased's age at the time of the murder, race, relationship to interviewee, and the deceased's relationship to the murderer, if known. For Parts 34-55, respondents were asked about their job titles, years in those positions, number of murder cases handled in the past year, number of murder cases handled over the course of their career, and whether they thought the criminal justice system could help to heal the harm of people who had lost loved ones to murder. All interviews (Parts 1-55) were tape-recorded and later transcribed by the interviewer, who replaced actual names of individuals, neighborhoods, cities, counties, or any other identifiable names with pseudonyms.